Regio- and stereoselective synthesis of new substituted tetrahydrocarbazoles and carbazoles using diels-alder reactions - Hingane, Dattatray G.; Goswami, Shailesh K.; Puranik, Vedavati G.; Kusurkar, Radhika S. (Synthetic Communications, 2012)
Diels-Alder reactions of 3-vinylindoles were carried out with methyl acrylate and N-phenylmaleimide as dienophiles under microwave conditions to furnish unreported tetrahydrocarbazoles regio- and stereoselectively in good yields. Further dehydrogenation resulted in new substituted carbazoles.
Keywords: Carbazoles; regio- and stereoselective Diels-Alder reactions; tetrahydrocarbazoles